The Effect of Blood-Derived Products on the Chondrogenic and Osteogenic Differentiation Potential of Adipose-Derived Mesenchymal Stem Cells Originated from Three Different Locations - Markus Neubauer; Olga Kuten; Christoph Stotter; Karina Kramer; Andrea De Luna; Thomas Muellner; Zsombor Lacza; Stefan Nehrer (Stem Cells International, 2019)
Background. Adipose-derived mesenchymal stem cells (AD-MSCs) from fat tissue considered “surgical waste” during joint surgery may provide a potent source for regenerative medicine. Intra-articular, homologous fat tissue (Hoffa’s fat pad, pouch fat) might possess a superior chondrogenic and osteogenic differentiation potential in comparison to extra-articular, nonhomologous fat. Blood products might further enhance this potential. Methods. AD-MSCs were isolated from fat tissue of 3 donors from 3 locations each, during total knee replacement. Isolated cells were analyzed via flow cytometry. Cells were supplemented with blood products: two types of platelet-rich plasma (EPRP—PRP prepared in the presence of EDTA; CPRP—PRP prepared in the presence of citrate), hyperacute serum (hypACT), and standard fetal calf serum (FCS) as a positive control. The viability of the cells was determined by XTT assay, and the progress of differentiation was tested via histological staining and monitoring of specific gene expression. Results. Blood products enhance ex vivo cell metabolism. Chondrogenesis is enhanced by EDTA-PRP and osteogenesis by citrate PRP, whereas hyperacute serum enhances both differentiations comparably. This finding was consistent in histological analysis as well as in gene expression. Lower blood product concentrations and shorter differentiation periods lead to superior histological results for chondrogenesis. Both PRP types had a different biological effect depending upon concentration, whereas hyperacute serum seemed to have a more consistent effect, independent of the used concentration. Conclusion. (i) Blood product preparation method, (ii) type of anticoagulant, (iii) differentiation time, and (iv) blood product concentration have a significant influence on stem cell viability and the differentiation potential, favouring no use of anticoagulation, shorter differentiation time, and lower blood product concentrations. Cell-free blood products like hyperacute serum may be considered as an alternative supplementation in regenerative medicine, especially for stem cell therapies.